2013
DOI: 10.1111/liv.12328
|View full text |Cite
|
Sign up to set email alerts
|

Conophylline suppresses hepatic stellate cells and attenuates thioacetamide‐induced liver fibrosis in rats

Abstract: Conophylline suppresses HSC and induces apoptosis in vitro. CnP also attenuates formation of the liver fibrosis induced by TAA in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 37 publications
3
19
0
Order By: Relevance
“…We previously reported that CnP suppressed liver fibrosis induced by thioacetamide through the suppression of hepatic stellate cells . Similarly, in the present study, CnP suppressed the desmoplastic changes in tumors that consisted of pancreatic cancer cells and CAF in a mouse xenograft model.…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…We previously reported that CnP suppressed liver fibrosis induced by thioacetamide through the suppression of hepatic stellate cells . Similarly, in the present study, CnP suppressed the desmoplastic changes in tumors that consisted of pancreatic cancer cells and CAF in a mouse xenograft model.…”
Section: Discussionsupporting
confidence: 83%
“…We previously reported that CnP suppressed liver fibrosis induced by thioacetamide through the suppression of hepatic stellate cells. 10 Similarly, in the present study, CnP suppressed the desmo- cells was significantly higher than that of SUIT-2 cells alone. E, α-SMA-positive stained area of tumors consisting of SUIT-2 + hPSC5 cells was significantly higher than that of SUIT-2 cells alone.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations